2014
DOI: 10.1016/j.foodchem.2013.08.115
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic profiling of the skin, pulp and seeds of Albariño grapes using hybrid quadrupole time-of-flight and triple-quadrupole mass spectrometry

Abstract: This paper describes for the first time a complete characterisation of the phenolic compounds in different anatomical parts of the Albariño grape. The application of high-performance liquid chromatography coupled with two complementary techniques, hybrid quadrupole time-of-flight and triple-quadrupole mass spectrometry, allowed the phenolic composition of the Albariño grape to be unambiguously identified and quantified. A more complete phenolic profile was obtained by product ion and precursor ion scans, while… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
85
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(95 citation statements)
references
References 41 publications
(39 reference statements)
8
85
1
1
Order By: Relevance
“…The gallic acid was identified and quantified using standard calibration curve, retention time and absorption spectra as mentioned in the Table 3. Di Lecce, et al 19 It may be concluded that free gallic are present in grape product below 2.0 mg/ 100 g. 3.…”
Section: Phenolic Composition Of Grape Leavesmentioning
confidence: 97%
“…The gallic acid was identified and quantified using standard calibration curve, retention time and absorption spectra as mentioned in the Table 3. Di Lecce, et al 19 It may be concluded that free gallic are present in grape product below 2.0 mg/ 100 g. 3.…”
Section: Phenolic Composition Of Grape Leavesmentioning
confidence: 97%
“…However, sometimes, the analyzed samples contained compounds that other varieties were lacking. For example, seeds from 'Albariño' a white variety grown in Vilafranca del Penedès totally lacked stilbenes (Di Lecce et al, 2014). The same situation was encountered in the case of trans-piceid, trans-resveratrol and cis-piceid in the skin of 'Cabernet Franc' and 'Cabernet Sauvignon' coming from Brazilian winemaking process in São Paulo (Barcia et al, 2014a).…”
Section: Total Anthocyanins Content (Tac)mentioning
confidence: 82%
“…This may account for the higher cisresveratrol concentration in 'Fetească neagră' flours compared to its trans-isomer. Previous studies have shown that not all seeds contain stilbenes, supporting the lack of these compounds in 'Italian Riesling' seed flours (Di Lecce et al, 2014). Because seed flour did not contain transresveratrol and the concentration in skin flour from 'Italian Riesling' is low, it might be possible that the compound did not rich the detection limit in the mixed flour of the same variety.…”
Section: Total Anthocyanins Content (Tac)mentioning
confidence: 82%
“…Generally we can say that the pomace contains more individual polyphenols than grape berries. This is caused mainly higher content of phenolic compounds found in skin and seed than in the pulp [Di Lecce et al 2014]. De la Cerda-Carrasco et al [2014] states, that pomaces from the white grape varieties showed significantly higher contents of polyphenols than pomaces from the red grape varieties.…”
Section: Resultsmentioning
confidence: 99%